Scaling Climate-smart Agriculture in North-central Vietnam - Simelton, Elisabeth; Dao, Tham Thi; Ngo, An The; Le Thi Tam (Science and Education Publishing Co., Ltd., 2017)
While the demand for climate-smart agriculture practices is rapidly growing in the 2010s, it remains vague in practice how to evaluate integrated farming systems, in particular. The study draws lessons learned from the My Loi climate-smart village, Ky Son commune, Ky Anh district, Ha Tinh province to explore the scalability potential to Ky Trung commune in the same district, and in the province. Specifically, we use mixed participatory field-based approaches to categorise current farming practices for the purpose of proposing context-specific climate-smart interventions, in addition to biophysical feasibility, policy support and expert consultations. Originating from local knowledge, five climate-smart agriculture models were derived with incremental implementation steps developed with technical expertise. While the specific components of the models are contextspecific, the technologies and this improved approach for identifying CSA practices can be generically applied.